USE OF AN ELECTRIC BOILER IN THE POWER SUPPLY SYSTEM TO PROVIDE THE SELF-CONSAMPTION OF THE REZIDENTIAL HOUSE WITH A HYBRID PHOTOVOLTAIC SYSTEM - ШАВЬОЛКІН, О. О.; ПІДГАЙНИЙ, М. О. (Technologies and Engineering, 2024)
Purpose. Increasing the efficiency of a hybrid photovoltaic system with a storage battery for the residential house needs by regulating the power of the electric boiler to maximize the use of photovoltaic battery energy for self-consumption, developing the principles of implementing an energy management system. Methodology. Planning the residential house energy consumption. Analysis of energy processes in the warm water supply system and in the electrical circuits of the photovoltaic power system using computer modeling to assess the effectiveness of energy management. Results. The structure of a boiler power regulator has been developed to ensure a current consumption close to a sinusoid for the entire adjustment range. Mathematical model of a boiler in a system for providing a house with warm water. Photovoltaic system structure with the introduction of a unit for forming the state of the storage battery charge and a boiler power regulator. Originality. Proposed to form the graph of storage battery state of charge with regulation of the power consumed by the boiler according to deviation from the specified graph. This will contribute to more complete utilization of the photovoltaic battery energy and decrease the consumption of electricity from the grid. The possibility of using energy consumption scenarios with planning family life activities during the day without significant restrictions is substantiated. The boiler model has been improved in the daily operating cycle with a warm water consumption schedule. The structure of the model of energy processes in the power supply system of a house for the daily cycle of operation has been developed with the boiler model introduction that takes into account its temperature regime. Practical value. The obtained solutions are the basis for the design of photovoltaic systems to provide the needs of residential homes.